Problematika Kejiwaan dalam Era Milenial dan Upaya Penanggulangannya - Yasin, Nur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Happiness is the hope of every human being. Happiness is a gift from God s.w.t. However, happiness is not a free product that is just obtained. It is the atmosphere and conditions that are fought for. Not a few people who risk their lives to achieve happiness. Some people have succeeded in achieving happiness and some others have failed. Or some groups of people have managed to achieve half happiness and some others have achieved complete happiness. And the measure of human happiness is found in his soul. A happy soul will feel calm and peace. And it is not because of the advancement or lack of progress, technological sophistication or backwardness Because it could be technological sophistication is the cause of human unhappiness. Living in millennial times does not guarantee that people will be happy despite the fantastic technology. Keywords: soul, technological progress, happines.